Post-traumatic Aortopulmonary Fistula after Bentall Procedure - Izzo, Daniela (J Cardiovasc Echogr, 2020)
Pseudoaneurysm complicated by aortopulmonary fistula (APF) after a Bentall procedure is extremely rare but potentially fatal, so timely diagnosis and treatment are critical. We present a subacute case of a post-traumatic APF which has had initial aspecific symptoms and later an acute worsening heart failure with chest pain not responding to medical treatment and requiring emergency surgery.